2015
DOI: 10.3892/ijo.2015.3220
|View full text |Cite
|
Sign up to set email alerts
|

FH535 suppresses the proliferation and motility of hepatocellular carcinoma cells

Abstract: Abstract. The Wnt signaling pathway is activated in hepatocellular carcinoma (HCC). This study investigated the effects of FH535, an inhibitor of the Wnt signaling pathway, on the proliferation and motility of HCC cells. HLF cells and PLC/ PRF/5 cells, HCC cells, were subjected to 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium, inner salt (MTS) assay with the addition of FH535. RNA was isolated from the cells and subjected to real-time quantitative PCR. Hematoxylin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…FH535 is a dual small molecule inhibitor of peroxisome proliferator-activated receptors (PPARs) and β-catenin/TCF/LEF 10 . Previous studies demonstrated that FH535 inhibits the growth of colon, lung, breast, pancreatic and hepatocellular cancer cells 10 - 13 , and represses pancreatic cancer xenograft growth and angiogenesis 14 .…”
Section: Introductionmentioning
confidence: 99%
“…FH535 is a dual small molecule inhibitor of peroxisome proliferator-activated receptors (PPARs) and β-catenin/TCF/LEF 10 . Previous studies demonstrated that FH535 inhibits the growth of colon, lung, breast, pancreatic and hepatocellular cancer cells 10 - 13 , and represses pancreatic cancer xenograft growth and angiogenesis 14 .…”
Section: Introductionmentioning
confidence: 99%
“…BLBP expression has been correlated with poor clinical outcome in several aggressive forms of cancer, such as renal cancer [ 22 ], hepatocellular carcinoma [ 30 ] and aggressive triple-negative breast cancer [ 31 ]. Since CSCs contribute to the aggressive nature of tumours and BLBP was a marker for these CSCs in ependymoma, we proposed that BLBP expression could be of robust prognostic value in ependymoma, a tumour for which prognostic markers are urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…FH535 is another antagonist that inhibits the Wnt/β-catenin signaling pathway and peroxisome proliferator-activator receptor (PPARγ and PPARδ) signaling [ 126 ]. This compound suppresses proliferation and motility of HCC cells through significant downregulation of cyclin D1 and MMP9 mRNA [ 127 ]. Additionally, FH535 is a potent therapeutic inhibitor that, upon combination with Sorafenib, exerts synergistic inhibition of proliferation and induction of apoptosis via enhancing cleaved poly (ADP-ribose) polymerase (PARP), inhibiting cyclin D1, Bcl-2, survivin, and c-MYC levels and reducing both mitochondrial respiration and glycolytic rates to disrupt the bioenergetics of HCC/LCSC cells [ 128 , 129 ].…”
Section: Interactions Of Lcscs Influencing Hcc and Therapeutic Strmentioning
confidence: 99%